The IAU Office of Astronomy for Development. (5th March 2015) - Govender, Kevin
Abstract: On 16 April 2011 the IAU's Office of Astronomy for Development (OAD) was launched jointly by the President of the IAU and the South African Minister of Science and Technology, at the South African Astronomical Observatory in Cape Town. This OAD was set up to realise the IAU's strategic plan which aims to use astronomy as a tool for development. Communicating astronomy with the public is one of the OAD's focus areas.